1973
DOI: 10.1113/jphysiol.1973.sp010356
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory and metabolic costs of continuous and intermittent exercise in man

Abstract: SUMMARY1. Cardiorespiratory and metabolic responses to paired patterns of continuous and intermittent exercise with the same average power output were studied in eight men. Heart rate, ventilation and pulmonary gas exchange were measured during the different patterns of exercise performed on a cycle ergometer. The recovery oxygen volume was measured over 30 min of loadless pedalling. Needle biopsy samples of the vastus lateralis muscle were taken before, during and after completion of the exercise for measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0
1

Year Published

1976
1976
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 35 publications
3
13
0
1
Order By: Relevance
“…The r 2 of >60% was consistent with but greater than that of 29% reported previously for explaining the determination of exercise endurance capacity with breathlessness intensity in competitive cyclists for performing intense continuous exercise (Harms et al 2000). Edwards et al (1973) reported that the ventilatory demands during exercise and recovery The time courses for the minute ventilation of 12-s exercise (ex) and 18-s recovery (rec) under CON and UL breathing conditions. All values from 2 to 6 min were significantly different from the value at the Final in the same trial.…”
Section: -S Exsupporting
confidence: 85%
“…The r 2 of >60% was consistent with but greater than that of 29% reported previously for explaining the determination of exercise endurance capacity with breathlessness intensity in competitive cyclists for performing intense continuous exercise (Harms et al 2000). Edwards et al (1973) reported that the ventilatory demands during exercise and recovery The time courses for the minute ventilation of 12-s exercise (ex) and 18-s recovery (rec) under CON and UL breathing conditions. All values from 2 to 6 min were significantly different from the value at the Final in the same trial.…”
Section: -S Exsupporting
confidence: 85%
“…Despite this, the rate of carbohydrate oxidation observed during intermittent exercise was apparently not slowed to the extent proposed by Essen et al (1977). This outcome is supported by the higher R and circulating lactate accumulation observed in intermittent intense compared to continuous submaximal exercise with the same average power output (Edwards et al 1973).…”
Section: Discussionmentioning
confidence: 75%
“…A method to stress the adaptive mechanisms of aerobic and anaerobic metabolisms during a training session is to design alternating periods of work and rest (Edwards et al, 1973). In this method, the work/rest ratio determines the physiological impact of intermittent efforts (Balsom, Seger, Sjodin & Ekblom, 1992;Hargreaves et al, 1998;Ratel, Bedu, Hennegrave, & Armstrong, 2002).…”
mentioning
confidence: 99%